Numerical Study on the Dynamics and Oxygen Uptake of Healthy and Malaria-Infected Red Blood Cells (Advances in Applied Mathematics and Mechanics, 2018)
Red blood cells (RBCs) are very important due to their role of oxygen transportfrom lungs. As the malaria parasite grows in the malaria-infected red blood cells(IRBCs), the properties of the cells change. In the present work, the oxygen uptake byRBCs and IRBCs at the pulmonary capillaries is simulated using a numerical techniquebased on the two-dimensional immersed interface method. The results for the oxygenuptake by a stationary single RBC have fair agreements with the previously reportedresults. The numerical results show that the malaria infection could significantly causedeterioration on the oxygen uptake by red blood cells. The results also suggest that theoxygen uptake by individual stationary RBC/IRBC would not be significantly affectedby the neighboring cells provided the separation distance is about the dimensionof the cell. Furthermore, it appears that the oxygen uptake by both RBCs and IRBCs isdominated by mass diffusion over the convection although the Peclet number is of theorder of unity.